2014
DOI: 10.4014/jmb.1309.09069
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Eugenol via Protocatechuic Acid by Thermophilic Geobacillus sp. AY 946034 Strain

Abstract: The metabolic pathway of eugenol degradation by thermophilic Geobacillus sp. AY 946034 strain was analyzed based on the lack of data about eugenol degradation by thermophiles. TLC, GC-MS, and biotransformation with resting cells showed that eugenol was oxidized through coniferyl alcohol, and ferulic and vanillic acids to protocatechuic acid before the aromatic ring was cleaved. The cell-free extract of Geobacillus sp. AY 946034 strain grown on eugenol showed a high activity of eugenol hydroxylase, feruloyl-CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The Geobacillus sp. was capable to grow with eugenol 0.01% (v/v) as the carbon resource and enhanced bacterial growth about eight times 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Geobacillus sp. was capable to grow with eugenol 0.01% (v/v) as the carbon resource and enhanced bacterial growth about eight times 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is showed that honeybees affect oral microbiome composition 24 . P. uorescens, P. putida, Corynebacterium sp., Fusarium solani, Byssochlamysfulva, and Penicillium simplicissimum, can degrade eugenol, an antibacterial agent present in clove 33 . A few eugenolconverting enzymes have been described, including vanillyl alcohol oxidase from Penicillium simplicissimum 34 , vanillin dehydrogenase from Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…To fulfill the huge market demand for flavor and fragrance, the relevant industries rely mostly on chemical methods of synthesis. Presently, various chemically synthesized flavors are available at cheap prices that lead to the generation of various harmful by‐products . So, taking into consideration the consumer's health interest, trends are shifting towards the use of green, eco‐friendly, and healthy processes for the generation of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…prices that lead to the generation of various harmful byproducts [2]. So, taking into consideration the consumer's health interest, trends are shifting towards the use of green, eco-friendly, and healthy processes for the generation of natural products.…”
Section: Introductionmentioning
confidence: 99%
“…Although mostly reported from mesophilic bacteria, a few thermophilic microorganisms have also been found to possess lignoaromatic-degrading potential (23)(24)(25)(26). Interestingly, immobilized protocatechuate 3,4-dioxygenase from Pseudomonas putida and dehydrogenases (DesV and LigV) from Sphingobium sp.…”
mentioning
confidence: 99%